Influence Of Drying Time And Temperature On Zirconium-Based Material (ZBM) Properties For 99Mo/99mTc Generator Development - Miftakul Munir; Endang Sarmini; Herlina Herlina; Anung Pujiyanto; Indra Saptiama; Kadarisman Kadarisman; Shella Kurnia (Balai Besar Kimia dan Kemasan, 2018)
Zirconium-based material (ZBM) has an important role in producing Technetium-99m (99mTc) due to its high adsorption capacity to Molybdenum-99 (99Mo). The adsorption capacity of the ZBM depends on the specific surface area which is influenced by several parameters in the synthesis process. This study aims to investigate the influence of drying time and temperature on the structure and specific surface area of the ZBM. Synthesis of the ZBM was carried out using zirconium chloride, 2-propanol, water and tetrahydrofuran at 75 °C, 90 °C and 120 °C and for 3 hr, 5 hr and 7 hr, respectively. Functional group and specific surface area of the ZBM was analyzed by FTIR and BET method, respectively. At the variation of drying time, the functional group pattern showed by FTIR spectra was not significantly different. The O-H group of the ZBM increased as the drying temperature decreases. At 75 and 90°C, the specific surface area increased as the function of time was increased but was decreased at 120°C. The highest surface area of the synthesized ZBM had a poor performance as a 99Mo/99mTc generator material, whereas the eluate met the required standard.